Build-up and characterisation of pollutants on urban impervious surfaces - Djukić, Aleksandar; Lekić, Branislava; Rajaković-Ognjanović, Vladana; Naunovic, Zorana; Prodanović, Dušan (Water science and technology, 2018)
This paper presents the results of the investigation of pollutant build-up on impervious surfaces of a parking lot in Belgrade, Serbia during the summer months. Contaminant build-up was found to be greater on asphalt surfaces directly exposed to vehicular traffic than on concrete walkways. The difference in the amounts of accumulated pollutants between asphalt and concrete were significant: for total solids (TS), total suspended solids (TSS), chemical oxygen demand (COD), heavy metals and total phosphorus (TP) accumulations were two to three times higher, while only 30% higher for total nitrogen (TN) and anions. Build-up of most of the measured parameters was best described by power functions. The highest surface loads were found for solids, COD, iron and zinc. A strong correlation was found between turbidity, TS, TSS, COD, heavy metals and phosphorus, while conductivity, nitrates and nitrites were weakly correlated to other parameters.